El significado de la negación paraconsistente - Palau, Gladys (Principia.)
This work agrees and supports the I. Hacking's thesis regarding the meaning of the logical constants accordingly with Gentzen's Introduction and Elimination Rules of Sequent Calculus, corresponding with the abstract conception of the notion of logical consequence. We would like to ask for the minimum rules that must satisfy a connective in order to be considered as a genuine negation. Mainly, we will refer to both da Costa's C-Systems and Priest's LP system. Finally, we will analyze the presentations of these systems within the Se- quent Logic to show that paraconsistent negation lacks of pure rules of negation-elimination and negation-introduction rules or that they involve other connectives, thus making difficult to assign an univocal meaning to paraconsistent negation.